A BRCA1‐interacting lncRNA regulates homologous recombination. (27th September 2015) - Sharma, Vivek; Khurana, Simran; Kubben, Nard; Abdelmohsen, Kotb; Oberdoerffer, Philipp; Gorospe, Myriam; Misteli, Tom
Abstract: Long non‐coding RNAs (lncRNAs) are important players in diverse biological processes. Upon DNA damage, cells activate a complex signaling cascade referred to as the DNA damage response (DDR). Using a microarray screen, we identify here a novel lncRNA, DDSR1 (DNA damage‐sensitive RNA1), which is induced upon DNA damage. DDSR1 induction is triggered in an ATM‐NF‐κB pathway‐dependent manner by several DNA double‐strand break (DSB) agents. Loss of DDSR1 impairs cell proliferation and DDR signaling and reduces DNA repair capacity by homologous recombination (HR). The HR defect in the absence of DDSR1 is marked by aberrant accumulation of BRCA1 and RAP80 at DSB sites. In line with a role in regulating HR, DDSR1 interacts with BRCA1 and hnRNPUL1, an RNA‐binding protein involved in DNA end resection. Our results suggest a role for the lncRNA DDSR1 in modulating DNA repair by HR. Synopsis: This study establishes a role for the lncRNA DDSR1 in maintaining genome stability. DDSR1 promotes homologous recombination by regulating recruitment of DNA repair factors to DSB after DNA damage. The lncRNA DDSR1 is induced upon DNA damage and interacts with BRCA1 and the RNA‐binding repair protein hnRNPUL1. DDSR1 and hnRNPUL1 interact to form a complex which prevents BRCA1 from promiscuous DNA binding and fine‐tunes the recruitment of BRCA1 to DSBs upon DNA damage. Absence of DDSR1 or hnRNPUL1 during DNA damage leads to increased recruitment of RAP80 and BRCA1 to DSBs to limit HR. Abstract : This study establishes a role for the lncRNA DDSR1 in maintaining genome stability. DDSR1 promotes homologous recombination by regulating recruitment of DNA repair factors to DSB after DNA damage.